Using the Microsoft Office Web Apps - McFedries, Paul (Que, 2010)
Using the Microsoft Office Web Apps brings you over 30 media elements detailing everything from how to access and customize them to collaborating and sharing your work. Watching these videos is the fastest way to get comfortable with the newest way to use Microsoft Office. Topics covered include signing up for a Windows Live ID, organizing your SkyDrive folders, working with SharePoint 2010, inviting your Facebook friends to your SkyDrive network, formatting your documents, downloading a snapshot of an Excel workbook, hiding a slide in PowerPoint, using tags to build a to-do list in OneNote, and much, much more!